Method for preparing tin-based perovskite solar cell through double-stage reduction strategy

Through a two-stage reduction strategy, thiosulfate is used to reduce Sn4+ and iodine element in the solution and film stages, the oxidation easiness and stability of tin-based perovskite solar cells is solved, and high efficiency and long-term stability are improved.

CN119300685AInactive Publication Date: 2025-01-10SUZHOU UNIV

Patent Information

Application Number
CN202411320909.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the oxidation ease, tin-based perovskite solar cells have low efficiency and poor stability. The existing reducing agents are toxic and have limited effects, making it difficult to effectively improve their performance and stability.

Method used

The two-stage reduction strategy is adopted, using thiosulfate as an additive to reduce Sn4+ to Sn2+ in the solution stage, and continue to reduce the iodine element in the film stage, reducing the tin vacancy and iodine element content, and improving the stability of the perovskite film.

Benefits of technology

Significantly improves the photoelectric conversion efficiency and storage stability of tin-based perovskite solar cells, reduces the decomposition rate, improves the carrier life and filling factor, reaches 14.78% efficiency and maintains 90% initial efficiency for long-term storage and in use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300685A_ABST
    Figure CN119300685A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a tin-based perovskite solar cell through a double-stage reduction strategy. The method comprises the following steps that S1, a hole transport layer is prepared on an anode substrate; s2, stannous fluoride, formamidine hydriodate, p-fluorophenethyl ammonium bromide, stannous iodide and thiosulfate are dissolved in an organic solvent for a reaction, a perovskite solution is obtained, the hole transport layer is coated with the perovskite solution, and a perovskite layer is obtained; s3, preparing an electron transport layer on the perovskite layer; and S4, sequentially preparing a hole barrier layer and a cathode electrode on the electron transport layer to obtain the tin-based perovskite solar cell. According to the method, the decomposition rate of the perovskite thin film under air and illumination is reduced, sustainable dynamic reduction is achieved by taking thiosulfate as an additive, and the storage stability and the operation stability of the tin-based perovskite solar cell are greatly improved through the dynamic sustainable behavior.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a method for preparing a tin-based perovskite solar cell using a dual-stage reduction strategy. Background Art

[0002] The power conversion efficiency of lead-based perovskite solar cells has increased significantly to over 26% in the past decade. However, the toxicity of lead itself poses a great potential problem for environmental and biological safety. Based on this, tin has become a favorable substitute for lead due to its lower toxicity and the same extranuclear electron configuration as lead. In addition, tin-based perovskites also have a more ideal band gap and are expected to reach near the theoretical efficiency limit of single-junction devices, making them the most promising lead-free perovskite material.

[0003] However, Sn is more susceptible to oxidation than Pb due to its lack of lanthanide contraction. 2+ Oxidation to Sn 4+ A large number of Sn vacancies will be generated. These tin vacancies lead to unfavorable p-type self-doping and non-radiative recombination, which reduces the quality of perovskite films and causes structural degradation. This results in the theoretical efficiency of tin-based perovskites being higher than that of lead-based perovskites, but the actual efficiency is much lower than that of lead-based perovskites. At the same time, during the placement and illumination process, perovskite solar cells will gradually release iodine ions and turn into iodine elements, which will accelerate the Sn 2+ The oxidation process of perovskite will also migrate to other transport layers, accelerating the degradation of perovskite solar cells. Moreover, when encountering water and oxygen, the degradation of perovskite will be further accelerated.

[0004] Over the years, different strategies have been designed to address these issues, including composition engineering, additive engineering, and device structure engineering. Unlike interface treatment, the use of reducing agents in the precursor preparation stage can effectively reduce Sn 4+ The presence of substances and inhibiting their formation in subsequent stages, such as Sn powder, hydrazine salts (including hydrazine dihydrochloride, hypophosphite, etc.), Sn (II) halides and Lewis bases (including hydroquinone sulfonic acid, gallic acid, etc.). However, these reducing agents usually involve highly toxic hydrazine compounds and can only achieve single-stage reduction. In addition, the introduction of these reducing agents does not significantly improve the stability of the device. Therefore, exploring suitable reduction strategies is of great significance for improving the performance and stability of perovskite solar cells. Summary of the invention

[0005] In order to solve the above technical problems, the primary purpose of the present invention is to provide a method for preparing tin-based perovskite solar cells using a dual-stage reduction strategy, which can improve the photoelectric conversion efficiency and operating stability of tin-based perovskite solar cells.

[0006] Another object of the present invention is to provide a tin-based perovskite solar cell prepared by the above method.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing a tin-based perovskite solar cell using a dual-stage reduction strategy comprises the following steps:

[0009] S1. Preparing a hole transport layer on an anode substrate;

[0010] S2. dissolving stannous fluoride (SnF2), formamidine hydroiodide (FAI), p-fluorophenethylammonium bromide (pF-PEABr), stannous iodide (SnI2) and thiosulfate in an organic solvent for reaction to obtain a perovskite solution, coating the perovskite solution on the hole transport layer described in S1 to obtain a perovskite layer; the concentration of the thiosulfate in the organic solvent is 0.05-0.4 mg / mL;

[0011] S3. Preparing an electron transport layer on the perovskite layer described in S2;

[0012] S4. A hole blocking layer and a cathode electrode are sequentially prepared on the electron transport layer described in S3 to obtain a tin-based perovskite solar cell.

[0013] The present invention provides a method for preparing tin-based perovskite solar cells using a dual-stage reduction strategy, in which thiosulfate is used as an additive to achieve sustainable dynamic reduction. In the solution stage, the thiosulfate ions in the thiosulfate convert the generated Sn into 4+ Reduction to Sn 2+ , and a series of oxidation products are produced, most of which are reducing, and continue to reduce the produced iodine together with the remaining thiosulfate in the next film stage.

[0014] Furthermore, in step S1, the anode substrate includes a fluorine-doped tin oxide (FTO) substrate.

[0015] In a specific implementation manner, the FTO substrate is cleaned, dried, and subjected to ultraviolet treatment.

[0016] Furthermore, the material of the hole transport layer includes poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS).

[0017] Furthermore, in step S1, the hole transport layer is spin-coated on the anode substrate and then annealed.

[0018] Furthermore, the spin coating method is: firstly spin coating at a rotation speed of 400-600 rpm for 10-20 s, and then spin coating at a rotation speed of 4000-5000 rpm for 40-60 s.

[0019] Furthermore, the annealing temperature is 130-150° C., and the annealing time is 10-20 min.

[0020] Furthermore, in step S2, the mass ratio of stannous fluoride to thiosulfate is (10-15):(0.05-0.4).

[0021] Furthermore, in step S2, the thiosulfate is selected from one or more of potassium thiosulfate, sodium thiosulfate and ammonium thiosulfate.

[0022] Furthermore, in step S2, the organic solvent is dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO), and when DMF and DMSO are used as a mixed solvent, the volume ratio of DMF to DMSO is 4:1.

[0023] Furthermore, in step S2, the perovskite solution is spin-coated on the hole transport layer, and the perovskite layer is obtained after annealing.

[0024] Furthermore, the spin coating has a rotation speed of 5000-5500 rpm, and the anti-solvent is added 20-25 seconds after the start of the spin coating, and the spin coating is continued for 25-30 seconds before annealing at 90-110° C. for 10-15 minutes.

[0025] Further, the anti-solvent comprises chlorobenzene (CB).

[0026] Furthermore, in step S3, the material of the electron transport layer includes fullerene and its derivatives, such as ICBA, PCBM, C60, etc.

[0027] Furthermore, the electron transport layer is prepared by spin coating, the spin coating speed is 1500-2500 rpm, and the spin coating time is 40-50 s.

[0028] Furthermore, in step S4, a hole blocking layer and a cathode electrode are prepared in sequence by using a thermal evaporation deposition method.

[0029] Furthermore, the material of the hole blocking layer includes bathocuproine (BCP).

[0030] Furthermore, the cathode electrode includes a silver (Ag) electrode.

[0031] Furthermore, the thickness of the hole transport layer is 30-40 nm, the thickness of the perovskite layer is 300-400 nm, the thickness of the electron transport layer is 30-40 nm, the thickness of the hole blocking layer is 8-10 nm, and the thickness of the cathode electrode is 100-110 nm.

[0032] The present invention also protects the tin-based perovskite solar cell prepared by the above method.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The method for preparing tin-based perovskite solar cells using a dual-stage reduction strategy provided by the present invention uses thiosulfate as an additive to achieve sustainable dynamic reduction. Thiosulfate is a simple, low-cost, non-toxic material. This method not only reduces the content of tetravalent tin in the solution stage and improves the stability of the solution, but also reduces the content of iodine in the film, indirectly inhibits the generation of tin vacancies, and improves the stability of the perovskite film.

[0035] 2. The method for preparing tin-based perovskite solar cells using a dual-stage reduction strategy provided by the present invention reduces the decomposition rate of the perovskite film under air and light. This dynamic sustainable behavior greatly improves the storage stability and operation stability of the tin-based perovskite solar cells.

[0036] 3. The tin-based perovskite solar cell provided by the present invention has a high carrier lifetime and low defect state density, which not only reduces the loss of open circuit voltage, but also improves the fill factor, so that its photoelectric conversion efficiency reaches 14.78% BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the mechanism of action of the double-stage reduction provided by the present invention.

[0038] Figure 2 This is a graph showing the JV performance test results of the tin-based perovskite solar cells prepared in Examples 1 to 5 and Comparative Examples 1 to 4.

[0039] Figure 3 Sn in the perovskite solution prepared in Example 1 and Comparative Example 1 4+ The data of Sn content and I2 content in the perovskite layer changing with time; where a is the Sn content of the perovskite solution under air conditions 4+ a is a data graph showing the change of I2 content over time, b is a data graph showing the change of I2 content over time in the perovskite layer under illumination conditions in a nitrogen atmosphere.

[0040] Figure 4The transient photoluminescence spectra and DLCP test spectra of the tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1; wherein a is the transient photoluminescence spectrum, and b is the DLCP test spectrum.

[0041] Figure 5 Storage stability curves of the tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1 stored in a nitrogen box for 2000 hours.

[0042] Figure 6 This is a graph showing the operating stability of the tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1 under AM 1.5G sunlight. DETAILED DESCRIPTION

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0045] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0046] In the following examples and comparative examples, FTO substrate and FAI were purchased from Liaoning Advanced Election Technology Co., Ltd. pF-PEABr and thiosulfate were purchased from Xi'an Biolight Company SnI2 was purchased from Libo New Energy Technology Co., Ltd. SnF2 was purchased from Aldrich ICBA was purchased from 1-Material DMSO, DMF and CB were purchased from Alfa Aesar Ltd.

[0047] Example 1

[0048] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag by a dual-stage reduction strategy comprises the following steps:

[0049] S1. Prepare a 30nm PEDOT:PSS layer on an FTO substrate: The FTO substrate was repeatedly ultrasonically cleaned three times with deionized water, acetone, and ethanol, and then baked for 20 minutes to completely remove the solvent and moisture. It was treated with UV lamp and ozone for 30 minutes, and the PEDOT:PSS layer was spin-coated on the FTO substrate, first at 500rpm for 10s, then at 4500rpm for 50s, and annealed at 140°C for 15 minutes to obtain the PEDOT:PSS layer.

[0050] S2. Prepare a 400nm Perovskite layer on the PEDOT:PSS layer described in S1: dissolve 12.48mg SnF2, 137.6mg FAI, 17.6mg pF-PEABr, 298mg SnI2 and 0.08mg K2S2O3 in 1mL of a mixed solvent of DMF and DMSO (i.e., the concentration of K2S2O3 is 0.08mg / mL), wherein the volume ratio of DMF to DMSO is 4:1, and stir overnight at room temperature to obtain a perovskite solution; statically coat 45μL of the perovskite solution on the PEDOT:PSS layer, the spin coating speed is 5000rpm, add 210μL of CB dropwise 20s after the start of spin coating, continue spin coating for 30s, then transfer to a heating table, anneal at 100°C for 10min to obtain a Perovskite layer.

[0051] S3. Prepare a 30 nm ICBA layer on the Perovskite layer described in S2: dissolve 20 mg ICBA powder in 1 mL CB, stir overnight at room temperature to obtain an ICBA solution; statically coat 45 μL ICBA solution on the Perovskite layer, spin coat at 2000 rpm for 40 seconds, and anneal at 80°C for 5 minutes to obtain an ICBA layer.

[0052] S4. A BCP layer and an Ag electrode are sequentially prepared on the ICBA layer described in S3: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared using vacuum evaporation technology.

[0053] Example 2

[0054] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.05 mg / mL.

[0055] Example 3

[0056] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.1 mg / mL.

[0057] Example 4

[0058] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.2 mg / mL.

[0059] Example 5

[0060] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.4 mg / mL.

[0061] Comparative Example 1

[0062] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag by a dual-stage reduction strategy comprises the following steps:

[0063] S1. Prepare a 30nm PEDOT:PSS layer on an FTO substrate: The FTO substrate was repeatedly ultrasonically cleaned three times with deionized water, acetone, and ethanol, and then baked for 20 minutes to completely remove the solvent and moisture. It was treated with UV lamp and ozone for 30 minutes, and the PEDOT:PSS layer was spin-coated on the FTO substrate, first at 500rpm for 10s, then at 4500rpm for 50s, and annealed at 140°C for 15min.

[0064] S2. Prepare a 400nm Perovskite layer on the PEDOT:PSS layer described in S1: dissolve 12.48mg SnF2, 137.6mg FAI, 17.6mg pF-PEABr and 298mg SnI2 in 1mL of a mixed solvent of DMF and DMSO, wherein the volume ratio of DMF to DMSO is 4:1, and stir overnight at room temperature to obtain a perovskite solution; statically coat 45μL of the perovskite solution on the PEDOT:PSS layer at a spin coating speed of 5000rpm, add 210μL of CB dropwise 20s after the start of spin coating, continue spin coating for 30s, then transfer to a heating table and anneal at 100°C for 10min to obtain a Perovskite layer.

[0065] S3. Prepare a 30 nm ICBA layer on the Perovskite layer described in S2: dissolve 20 mg ICBA powder in 1 mL CB, stir overnight at room temperature to obtain an ICBA solution; statically coat 45 μL ICBA solution on the Perovskite layer, spin coat at 2000 rpm for 40 seconds, and anneal at 80°C for 5 minutes to obtain an ICBA layer.

[0066] S4. A BCP layer and an Ag electrode are sequentially prepared on the ICBA layer described in S3: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared using vacuum evaporation technology.

[0067] Comparative Example 2

[0068] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.6 mg / mL.

[0069] Comparative Example 3

[0070] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 0.8 mg / mL.

[0071] Comparative Example 4

[0072] A method for preparing a tin-based perovskite solar cell with an inverted structure of FTO / PEDOT:PSS / Perovskite / ICBA / BCP / Ag using a two-stage reduction strategy is basically the same as Example 1, except that in step S2, the concentration of K2S2O3 is 1 mg / mL.

[0073] Figure 1 A schematic diagram of the mechanism of action of the two-stage reduction provided by the present invention. In the first stage, tetravalent tin is reduced to divalent tin in the solution and a reducing product is generated. In the second stage of the film, these reducing substances reduce iodine to iodide ions, ultimately improving the photoelectric conversion efficiency and stability of the tin-based perovskite solar cell.

[0074] The tin-based perovskite solar cells prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested for short-circuit current density-open-circuit voltage (JV) performance by using a Keithley 2400 source meter under sunlight irradiation with an air mass (AM) of 1.5G. The test results are shown in FIG. Figure 2 As shown, it can be seen that the highest PCEs of Comparative Example 1 and Example 1 reached 12.35% and 14.78%, respectively. The performance of the optimized tin-based perovskite solar cell was significantly improved, and the performance of the tin-based perovskite solar cell prepared in Example 1 was the best.

[0075] Example 1 (W / S2O3 2- ) and Comparative Example 1 (W / O S2O3 2- The perovskite solution and perovskite layer prepared by the method were placed in air and nitrogen atmosphere respectively to observe the Sn content in the perovskite solution. 4+ Content and the change of I2 content in the perovskite layer over time, such as Figure 3 As shown, the Sn in the perovskite solution of Example 1 4+ The content of I2 in the perovskite layer is significantly lower than that in Comparative Example 1, proving that thiosulfate brings about a two-stage reduction.

[0076] Figure 4 The transient photoluminescence spectra and driver level capacitance analysis (DLCP) test spectra of the tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 4 As can be seen in a, the carrier lifetime of the perovskite layer increases after thiosulfate treatment; Figure 4 As can be seen in b, the defects of the perovskite solar cell after thiosulfate treatment are passivated, reducing the defect state density.

[0077] Figure 5 The tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1 were stored in a nitrogen box for 2000 hours for stability, and the photoelectric conversion efficiency was measured every 100 hours. The devices after final treatment still maintained 99% of the initial efficiency.

[0078] Figure 6The working stability of the tin-based perovskite solar cells prepared in Example 1 and Comparative Example 1 under AM 1.5G sunlight irradiation, after treatment, the initial efficiency is still maintained at 90% after 628 hours. Compared with the untreated device, the stability of the device is greatly improved.

[0079] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing tin-based perovskite solar cells using a dual-stage reduction strategy, characterized in that: The following steps are involved: S1. Preparing a hole transport layer on an anode substrate; S2. dissolving stannous fluoride, formamidine hydroiodide, p-fluorophenethylammonium bromide, stannous iodide and thiosulfate in an organic solvent for reaction to obtain a perovskite solution, coating the perovskite solution on the hole transport layer described in S1 to obtain a perovskite layer; the concentration of the thiosulfate in the organic solvent is 0.05 to 0.4 mg / mL; S3. Preparing an electron transport layer on the perovskite layer described in S2; S4. A hole blocking layer and a cathode electrode are sequentially prepared on the electron transport layer described in S3 to obtain a tin-based perovskite solar cell.

2. The method according to claim 1, characterized in that In step S1, a hole transport layer is spin-coated on an anode substrate and then annealed.

3. The method according to claim 2, characterized in that The spin coating method is: firstly spin coating at a rotation speed of 400-600 rpm for 10-20 seconds, and then spin coating at a rotation speed of 4000-5000 rpm for 40-60 seconds.

4. The method according to claim 2, characterized in that: The annealing temperature is 130-150° C., and the annealing time is 10-20 minutes.

5. The method according to claim 1, characterized in that In step S2, the mass ratio of stannous fluoride to thiosulfate is (10-15):(0.05-0.4).

6. The method according to claim 1, characterized in that In step S2, the thiosulfate is selected from one or more of potassium thiosulfate, sodium thiosulfate and ammonium thiosulfate.

7. The method according to claim 1, characterized in that In step S2, the perovskite solution is spin-coated on the hole transport layer, and the perovskite layer is obtained after annealing.

8. The method according to claim 7, characterized in that The rotation speed of the spin coating is 5000-5500 rpm, the anti-solvent is added 20-25 seconds after the start of the spin coating, the spin coating is continued for 25-30 seconds, and then the annealing treatment is performed at 90-110° C. for 10-15 minutes.

9. The preparation method according to claim 1, characterized in that: In step S3, the electron transport layer is prepared by spin coating, the spin coating speed is 1500-2500 rpm, and the spin coating time is 40-50 s.

10. A tin-based perovskite solar cell prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Perovskite ink, large-area perovskite thin film and battery device

    CN115286949A

  • Tin-based perovskite thin film, preparation method thereof and solar cell comprising thin film

    CN116209333A

  • Tin-based perovskite photovoltaic device and preparation method thereof

    CN117729783A

  • Preparation method of p-type semiconductor film, p-type semiconductor film, manufacturing method of perovskite solar cell, and perovskite solar cell

    JP2024027324A

Cited By

  • Thiosulfate-doped low-stress room-temperature flexible perovskite thin film deposition method

    CN120897651A

  • Method for deposition of low-stress room-temperature flexible perovskite thin films doped with thiosulfate

    CN120897651B